2019
DOI: 10.1111/ans.15373
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term significance of an anastomotic leak in patients undergoing an ultra‐low anterior resection for rectal cancer

Abstract: Background: Australia has one of the highest rates of colorectal cancer worldwide. Despite technological advances in colorectal surgery, anastomotic leaks (ALs) continue to cause significant morbidity and mortality. Ultra-low anterior resections (ULARs) carry the highest prevalence of AL. The aim of the study is to evaluate the incidence, treatment and consequences of AL following ULAR for colorectal cancer from a single colorectal unit. Methods: This is a retrospective evaluation of prospectively collected da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, Anastomotic leakage after rectal cancer is still controversial for the long‐term oncological outcome. Some research show that it is no significant correlation between anastomotic leakage and long‐term oncological outcome 13‐62 …”
Section: Introductionmentioning
confidence: 99%
“…However, Anastomotic leakage after rectal cancer is still controversial for the long‐term oncological outcome. Some research show that it is no significant correlation between anastomotic leakage and long‐term oncological outcome 13‐62 …”
Section: Introductionmentioning
confidence: 99%
“…Since Heald et al proposed total mesorectal excison (TME) in 1982, the clinical outcomes of middle and low rectal cancer have been signi cantly improved [14,15], but anastomotic leakage is still an important factor affecting the short-term and long-term postoperative outcomes of rectal cancer, and greatly increases the total cost of treatment [16][17][18]. It has been reported that the incidence of anastomotic leakage after rectal cancer surgery is 5% ~ 26% [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Since Heald et al proposed total mesorectal excision in 1982, the clinical outcomes of middle and low rectal cancer have signi cantly improved [14,15]. This improvement is mainly due to reduced local recurrence [16]; however, anastomotic leakage is still an important factor affecting the short and longterm postoperative outcomes of rectal cancer, in addition to increasing the total cost of treatment [17][18][19]. It has been reported that the incidence of anastomotic leakage after rectal cancer surgery is between 5-26% [20,21].…”
Section: Discussionmentioning
confidence: 99%